Influence of Sputtering Pressure on the Conductivity and Transparency of Aluminum-Doped Zinc Oxide Films - Park, Hyeong Gi; Heo, Keun; Lee, Jae Hyun; Yi, Junsin (Applied Science and Convergence Technology, 2023)
Aluminum-doped zinc oxide (AZO) films are promising candidates for transparent electronics due to their low resistivity, high transmittance, and long-term stability. In this study, we investigated the impact of sputtering pressure on resistivity saturation in AZO films that are deposited by using radio frequency magnetron sputtering on transparent glass at room-temperature (RT). An X-ray diffraction analysis reveals that RT-deposited AZO (RT-AZO) films prepared at a pressure of 20 Pa exhibit a predominant orientation along the a-axis, favoring the (100) direction, as well as the lowest resistivity value of ∼ 4 × 10−3Ω⋅cm and the highest transmittance (95 %) in the visible range. These findings highlight the potential of our deposition approach for producing highly oriented (100) RT-AZO films, paving the way for their application to low-cost transparent electronics.
Keywords: Aluminum-doped zinc oxide; Radio frequency magnetron sputtering; Room-temperature; Transparent electronics